The value of local ecological knowledge to guide tree species selection in tropical dry forest restoration. Issue 4 (12th March 2021) - Fremout, Tobias; Gutiérrez‐Miranda, Claudia Elena; Briers, Siebe; Marcelo‐Peña, José Luis; Cueva‐Ortiz, Eduardo; Linares‐Palomino, Reynaldo; La Torre‐Cuadros, María de los Ángeles; Chang‐Ruíz, Janette Cristina; Villegas‐Gómez, Tania Libertad; Acosta‐Flota, Arantza Helen; Plouvier, Dominiek; Atkinson, Rachel; et al.
Abstract : Forest restoration projects involving active planting should prioritize species that are useful to local communities, while also considering species' threat status and resistance to local stress factors, but scientific knowledge on these criteria is scarce, especially in understudied tropical ecosystems. We hypothesized that local ecological knowledge can help to fill this gap. Through interviews with 47 local experts and 197 randomly selected households in 8 rural communities of the tropical dry forests of northwestern Peru and southern Ecuador, we identified the species perceived as most useful, most threatened, and most resistant to local stress factors. To better understand the studied local ecological knowledge, we also explored the following research questions and their implications for species selection decisions: (1) How does species' potential usefulness compare to their active use? (2) How does species' perceived threat status relate to their usefulness? (3) Does local knowledge on species' resistance to local stress factors corroborate scientific knowledge? We found large differences between the potential and active use of species and illustrate how data on both can yield useful insights. Furthermore, we found that species' perceived threat status was mainly linked to their usefulness for construction wood, and that the vast majority of local perceptions on species' threat status and stress resistance coincided with scientific knowledge. Our findings illustrate the large potential of local ecological knowledge for improving species selection strategies and thereby increasing the success of forest restoration efforts worldwide.